Pembangunan Mail Server Menggunakan Docker Dan Mailu Pada Virtual Private Server (VPS) Berbasis Linux - Azri Irawan; Sunarsan Sitohang (Computer Science and Industrial Engineering, 2024)
Currently, almost all aspects of life have been reached by technology such as server services, one of which is mail servers. Mail server stands out because it is the most frequently used server function in various fields. However, there are still many organizations and individuals who use third party email services such as Google (gmail.com), Yahoo rather than using the organization's or individual's own domain, one of which is a business at PT. Pundi Mas Berjaya is Jova School. This results in fraud, data leaks, and so on. So research was carried out on developing a Mailu mail server using a Linux Virtual Private Server (VPS) with the aim of overcoming problems in a business by creating a mail server service for the Jova School business at PT. Pundi Mas Berjaya. The research method used in this research is qualitative and uses observation, interview and literature study data collection methods. The results of this research are that you can implement a mail server at Jova School at PT. Pundi Mas Berjaya, improves security, privacy, effectiveness and efficiency in communicating and conveying information.